2003
DOI: 10.1111/j.1365-2621.2003.tb09658.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Caramel at the Micrometer Scale

Abstract: The surface of caramel has been imaged using pulsed force atomic force microscopy (AFM) and scanning thermal microscopy, revealing shallow depressions in the surface of 1 to 10 m in dia that have a higher adhesion to the silicon AFM probe and a lower stiffness and different thermal character than the surrounding sample. This is consistent with the view of caramel as fat droplets within a matrix of sugars. As confirmation, the depressed regions were identified by infrared microscopy as consisting mainly of fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Sun et al [1226] found that annealing of octyltriethoxysilane films on glass at elevated temperature lead to breakup of films and formation of islands but coverage of the glass surfaces was still observed between islands according to stiffness and adhesion data. Morton et al [1227] found shallow depressions in the surface of caramel with 1-10 mm in diameter that exhibited higher adhesion to the silicon AFM probe and a lower stiffness than the surrounding sample. This is consistent with the view of caramel as fat droplets within a matrix of sugars.…”
Section: Pulsed Force Mode Atomic Force Microscopymentioning
confidence: 99%
“…Sun et al [1226] found that annealing of octyltriethoxysilane films on glass at elevated temperature lead to breakup of films and formation of islands but coverage of the glass surfaces was still observed between islands according to stiffness and adhesion data. Morton et al [1227] found shallow depressions in the surface of caramel with 1-10 mm in diameter that exhibited higher adhesion to the silicon AFM probe and a lower stiffness than the surrounding sample. This is consistent with the view of caramel as fat droplets within a matrix of sugars.…”
Section: Pulsed Force Mode Atomic Force Microscopymentioning
confidence: 99%
“…By probing the surface of samples with a nanometrical tip, AFM has been used to probe molecular interactions via force spectroscopy (Morris, Woodward, & Gunning, 2011). Moreover, AFM has been demonstrated as an ideal platform to develop advanced techniques for nanomechanical characterization of samples (Passeri, Rossi, Tamburri, & Terranova, 2013), the potential of which for the analysis of Young's modulus, complex elastic modulus, hardness, tip-sample adhesion force has been only marginally explored in food derived samples (Goode, Bowen, Akhtar, Robbins, & Fryer, 2013;Morton et al, 2003;Scramin et al, 2011;Zdunek & Kurenda, 2013). As an example, Fig.…”
Section: Scanning Probe Microscopy Based Techniques For Nanoscale Chamentioning
confidence: 99%
“…based technique which allows one to perform the quantitative characterization of mechanical parameters of soft samples (mainly, elastic modulus, tip-sample adhesion force and tip-sample dissipation) with nanometrical lateral resolution (Sahin & Erina, 2008;Sahin, Magonov, Su, Quate, & Solgaard, 2007). Also, thermal characterization at the nanoscale has been performed on caramel using SThM (Morton et al, 2003). Finally, even if only marginally, other SPM techniques have been used to study food derived samples, i.e., SNOM for the characterization of proteinsurfactant interactions by acquiring fluorescence images at sub-micrometer scale (Morris, 2004) and STM for the investigation of high molecular subunits of wheat glutenin (Tatham et al, 1999).…”
Section: Scanning Probe Microscopy Based Techniques For Nanoscale Chamentioning
confidence: 99%
“…If it is due to other reasons, one can scan faster (Eaton, 2010). If the sample is too sticky or too soft, an artifact due to multiple probe-sample contact points occurs (Morton et al, 2003;Sokolov, 2007). This problem is highly relevant to cells studies (Touhami, Jericho & Beveridge, 2004).…”
Section: Artifacts Related To the Sample Propertiesmentioning
confidence: 99%
“…The sample can be too sticky or too soft. In this case, artifacts due to multiple probe-sample contact points occur (Morton et al, 2003;Sokolov, 2007). AFM image of a charged nonconductive sample may not correspond to topography.…”
Section: Introductionmentioning
confidence: 99%